Combination of aspirin with essential fatty acids is superior to aspirin alone to prevent or ameliorate sepsis or ARDS. Issue 1 (December 2016) - Das, Undurti
Abstract It has been suggested that aspirin may be of benefit in treating sepsis and ARDS in view of its ability to block cyclo-oxygenase-1 (COX-1) and COX-2 activities; inhibit nuclear factor kappa B (NF-κB); enhance the production of endothelial nitric oxide (eNO) and lipoxin A4 (LXA4). Our previous studies revealed that plasma phospholipid content of arachidonic acid (AA) and eicosapentaenoic acid (EPA) is low in patients with sepsis. This implies that beneficial actions of aspirin in sepsis and ARDS is unlikely to be obtained in view of deficiency of AA and EPA, the precursors of LXA4 and resolvins respectively that are potent anti-inflammatory compounds and enhancers of eNO generation. In view of this, I propose that a combination of aspirin and AA and EPA (and possibly, docosahexaenoic acid, DHA) is likely to be superior in the management of sepsis and ARDS compared to aspirin alone. This suggestion is supported by the recent observation that trauma patients with uncomplicated recoveries had higher resolvin pathway gene expression and lower gene expression ratios of leukotriene: resolvin pathways.